Mortality from nonmalignant respiratory diseases among male workers in Norwegian ferroalloy plants - Hobbesland, Å; Kjuus, Helge; Thelle, DS (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'This study examined mortality from nonmalignant respiratory diseases among ferroalloy workers.' ' METHODS ': 'The cohort comprised 14 730 men employed for the first time in 1933--1990 and for at least 6 months in 1 of 12 plants. The duration of work in specific departments and exposure to amorphous silica in the ferrosilicon/silicon-metal (FeSi/Si-met) plants, estimated from a job-exposure matrix, were the main exposure variables. Deaths were observed during 1962--1990. The mortality was analyzed with the use of standardized mortality ratios (SMR) and internal comparisons of rates.' ' RESULTS ': 'Overall mortality from nonmalignant respiratory diseases was not increased, but mortality from bronchitis, emphysema, and asthma combined was significantly increased among the men with at least 3 years of FeSi/Si-met furnace work (SMR 1.82, 16 deaths). A Poisson regression analysis of the mortality from these causes among 6359 employees in the FeSi/Si-met plants showed a significant increase of 0.06 per unit of amorphous silica exposure observed 10--20 years after the exposure. Six men died of pneumonia while still employed in a ferromanganese/silicomanganese (FeMn/SiMn) plant. No corresponding deaths occurred among employees in FeSi/Si-met plants. Only 2 deaths from pneumoconiosis were observed in the total cohort.' ' CONCLUSION ': 'Among employees in FeSi/Si-met plants increased mortality from bronchitis, emphysema, and asthma may be associated with previous exposure to amorphous silica. Deaths from pneumonia among FeMn/SiMn workers may be associated with manganese exposure.
Keywords: amorphous silica; asthma; bronchitis; emphysema; ferrosilicon; lung disease; manganese; pneumonia